2015
DOI: 10.2147/ijn.s78321
|View full text |Cite|
|
Sign up to set email alerts
|

Bypassing the EPR effect with a nanomedicine harboring a sustained-release function allows better tumor control

Abstract: The current enhanced permeability and retention (EPR)-based approved nanomedicines have had little impact in terms of prolongation of overall survival in patients with cancer. For example, the two Phase III trials comparing Doxil ® , the first nanomedicine approved by the US Food and Drug Administration, with free doxorubicin did not find an actual translation of the EPR effect into a statistically significant increase in overall survival but did show less cardiotoxicity. In the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…For instance, nanocarriers can enhance localized delivery of therapeutic agents by incorporating transport enhancing components, such as targeting ligands and sustained/triggered-release systems, and by taking advantage of transport phenomena that appear on the nanoscale, e.g. reduced renal clearance and the enhanced permeability and retention effect [1, 2]. Studies have demonstrated that nanodelivery can substantially increase the tumor accumulation of small molecules [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nanocarriers can enhance localized delivery of therapeutic agents by incorporating transport enhancing components, such as targeting ligands and sustained/triggered-release systems, and by taking advantage of transport phenomena that appear on the nanoscale, e.g. reduced renal clearance and the enhanced permeability and retention effect [1, 2]. Studies have demonstrated that nanodelivery can substantially increase the tumor accumulation of small molecules [3, 4].…”
Section: Introductionmentioning
confidence: 99%